Novel Composite Materials for Lake Restoration: A New Approach Impacting on Ecology and Circular Economy - Miltiadis Zamparas (Sustainability, 2020)
The purpose of this study is to promote a new way of application composite materials to restore eutrophic waters. A new sustainable way of application is based on the “teabag” method, in which materials were placed in water-permeable bags and immersed in the water column in order to sorb phosphate—one of the main contributory element for the eutrophication problem. Particularly, the two composites materials of Phoslock™ (lanthanum-modified bentonite, LMB) and Bephos™ (Fe-modified bentonite, f-MB) were tested and bench-scale batch experiments were employed to investigate their sorption efficiency in the forms of slurry and teabag. The adsorption kinetics and the relevant adsorption isotherms were deployed, while the effect of the materials on turbidity and their aging were also investigated. Experimental results showed that Phoslock™ and Bephos™ (as teabag), being applied at initial concentration range: 0.05–5 mg/L, they sustained a maximum adsorption capacity of 7.80 mg/g and 25.1 mg/g, respectively, which are considered sufficient rates for P concentrations reported at natural aquatic ecosystems. At the same time this new method did not cause turbidity in the water column, since the material was not released into the water, thus, preventing potential harmful consequences for the living organisms. Moreover, the “teabag” method prevents the material to cover the lake bottom, avoiding the phenomenon of smothering of benthos. Βy teabag method, the materials can be collected for further applicability as soil improver or crops fertilizer. Finally, it was argued that the possibility to recycle Phoslock™ and Bephos™ materials for agricultural use is of paramount importance, sustaining also positive impacts on sustainable ecology and on the routes of circular economy (CE).